2021
DOI: 10.1101/2021.10.06.463409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncovering expression signatures of synergistic drug response using an ensemble of explainable AI models

Abstract: Complex machine learning models are poised to revolutionize the treatment of diseases like acute myeloid leukemia (AML) by helping physicians choose optimal combinations of anti-cancer drugs based on molecular features. While accurate predictions are important, it is equally important to be able to learn about the underlying molecular basis of anti-cancer drug synergy. Explainable AI (XAI) offers a promising new route for data-driven cancer pharmacology, combining highly accurate models with interpretable insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Moreover, the application of Explainable AI (XAI) in life sciences [21][22][23] , although widespread, often grapples with complex, multidimensional data. In this context, model ensembles offer a significant advantage, improving the quality and reliability of feature attribution 24 , thereby aligning with the growing emphasis on transparency and comprehension in AI models used for biological data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the application of Explainable AI (XAI) in life sciences [21][22][23] , although widespread, often grapples with complex, multidimensional data. In this context, model ensembles offer a significant advantage, improving the quality and reliability of feature attribution 24 , thereby aligning with the growing emphasis on transparency and comprehension in AI models used for biological data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, regarding classification algorithms (CA) for predicting response to therapy, a scalable ML approach has not been efficiently identified. Recently, investigators have reported on support vector machines ( Castillo et al , 2019 ; Gal et al , 2019 ; Lee et al , 2018 ), k-nearest neighbor ( Castillo et al , 2019 ; Gal et al , 2019 ; Lee et al , 2018 ), RF ( Castillo et al , 2019 ; Gal et al , 2019 ), artificial neural networks ( Janizek et al , 2021 ) and gradient boosting ( Janizek et al , 2021 ) for conducting these types of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Many feature extraction algorithms, or rather feature selection techniques, for gene expression data have been proposed, from the traditional use of principal component analysis (PCA; Gal et al , 2019 ) to customized techniques ( Castillo et al , 2019 ; Lee et al , 2018 ). Some of these works include the EXPRESS ( Janizek et al , 2021 ) algorithm that uses ensembles of XGBoost models and the Shapley Additive Explanation (SHAP) package to calculate a global feature importance ranking. Yap et al (2021) used SHAP to explain a convolutional neural network to classify samples on 47 different tissues based on RNA-seq count data and compared the genes identified by SHAP with differential expression analysis.…”
Section: Introductionmentioning
confidence: 99%